Is STEM Education Gender Neutral? An Analysis of Teachers’ Perceptions of Gender Differences in Five Countries - Mazur, Remigiusz; Walaszczyk, Ludmiła; Apostolatu, Rodica-Cristina; Beutner, Marc (Journal of Education Culture and Society, 2025)
Thesis. The authors investigate the extent to which STEM (Science, Technology, Engineering, Mathematics) education is perceived as gender-neutral by educators across Europe, with a focus on how these perceptions influence student engagement and the perpetuation of gender gaps. Methods. A mixed-methods approach was employed, combining quantitative survey data from 167 teachers in Germany, Poland, Romania, Türkiye, and Portugal with qualitative insights from focus group interviews. The study aimed to assess educators’ awareness of gender imbalances in STEM fields, their attitudes toward inclusivity, and the pedagogical practices they adopt in response to perceived disparities. Results. Findings indicate that while a majority of teachers acknowledge the existence of gender disparities in STEM education, their interpretations and proposed responses differ significantly. Some educators minimise the issue, while others emphasise its systemic nature. Conclusion. The results point to a lack of unified understanding and underscore the urgent need for professional development focused on gender-sensitive teaching strategies. The conclusion emphasises the pivotal role teachers play in either challenging or reinforcing stereotypes and highlights the necessity of integrating gender awareness into teacher training programs. Originality. This research offers a cross-national perspective on teachers’ perceptions of gender in STEM, contributing valuable insights into the social dynamics shaping educational equity.